Engineering, hydrological, and sedimentation studies of the Kankai River, eastern Nepal - Raghubanshi, UK (Journal of Nepal Geological Society, 2008)
With the development of human civilization and rapidly growing population the demand and uses of water resources is growing abruptly. Water resources have been used for domestic water supply, industrial use, irrigation and hydropower. For the country like Nepal where there is the spatial and temporal variations of water availability and the demand for various uses, there are the great challenge in water resources management and managing the conflicts in the allocation of water among the different water sectors as well as among different regions. Similarly, the sediment related issues of the watershed have to be addressed as well. Every year million of tons of sediment get transported by drainage networks in Nepal. The effect of temporal and spatial variation of hydrological conditions in diversified geographic condition creates variation in sediment transportations. The efficiency and workability of different water resource projects like Irrigation, Hydropower and Domestic water supply projects are badly affected by the sediment problems. If proper condition and relations between hydrological system and sediment problems are well known, the conflicts and the risks in water resources management can be minimized and proper planning and development of future water resources project can be done effectively and efficiently. The Kankai River is one of the class IIb type rainfed perennial river of eastern Nepal. The study area has warm temperate rainy climates with mild winter. Upper part of basin basically consists of granitic gneiss of Cambro-Ordovician age lower part consists of Quaternary rocks. The present study is basically focused on two parts. One is the hydrological analysis, which includes rainfall, discharge and climatic factor analysis; prediction of the flood, estimation of evapotranspiration, runoff, and also includes the open channel hydraulics and study of some hydraulic structures. Similarly second part includes some parts of sedimentation engineering which includes sediment properties, sediment sampling techniques, sediment yields, hydraulics of sediment transport and sediment routing. Rainfall Intensity in the study area is moderate to heavy. Potential Evapotranspiration (PET) obtained by Penman’s method show maximum PET during the month of May and minimum during January. Among different major crops, PET of rice is high (107.21 cm in total cropping period) and that of wheat is low with PET=38.90 cm. Annual runoff coefficient of the Kankai river basin is 0.65. For the different Hydraulic Structures and natural river channel with different structural geometry and variable slope values, the flow varies from Subcritical, Critical to Super-critical condition.The Kankai River is gravelly river with more than 60% gravel of gneiss and remaining other are of different metamorphic and sedimentary rocks. There is a seasonal, temporal and spatial variability of sediment yield in the watershed of the Kankai River. By applying the Regional Regression Relationship method, the sediment yield of Kankai River is estimated to be 0.148 million ton/year. Critical Bed Shear Stress varies from 0.589N/m2 for sand to 19.625 N/m2 for gravel. The shield parameter (dimensionless shear stress) varies from 0.7 to 0.021 for gravel. Mobility No. related to weight concentration of bed material load is calculated to be 0.2161.Sediment accumulation and transportation is influnced by hydrological activities and geological condition of watershed. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.18